Audit Energi Awal Pada Pompa Distribusi IPA Waribang II Perumda Air Minum Tirta Sewakadarma Kota Denpasar - Arif, Maulana Nur; Eddy Setiadi Soedjono (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The energy cost at Perumda Air Minum Tirta Sewakadarma reached Rp452/m³, exceeding the national average of Rp380.13/m³. Despite this, no energy audit has been conducted in accordance with established standards. This study aims to conduct a preliminary energy audit and assess opportunities to enhance energy efficiency, particularly at the distribution pump of IPA Waribang II. The research involved primary data collection through field observations and secondary data. The audit revealed SEC of 0.23 kWh/m³, which is good. However, total pump efficiency was only 44.23%, below the recommended minimum of 60%. The distribution pump’s capacity exceeds the IPA, prompting manual adjustment of motor speed using VSD to 1,250 rpm, down from its maximum 1,480 rpm, to match IPA output of 150 L/s. The optimization could is by forming a subzone aligned with IPA capacity and automating the VSD based on demand fluctuations. Alternatively, the pump could be replaced with one appropriately sized for the IPA. The voltage imbalance is 0.33%, indicating stable power supply. The power factor is measured at 0.91 and could be improved to 0.99 using capacitor bank to avoid reactive power penalties.